Stepping up Th1 immunity to control phagosomal bacteria. Issue 6 (June 2021) - Watts, Tania H.
Abstract : How does the immune system tailor effector function to particular threats? Krueger et al. reveal that infection with Salmonella enterica (SE), but not with influenza A virus (IAV), drives interleukin (IL)-12-dependent outgrowth of interferon (IFN)-γ hi type 1 T helper (Th1) cells, leading to superior protection against this phagosomal pathogen. Among these cells are ZEB2-dependent cytotoxic Th1 cells marked by CX3CR1 expression.